Solute chemistry and groundwater arsenic enrichment in southern part of Brahmaputra River Basin, India, adjacent to Indo-Burmese ranges - Verma, S.; Mukherjee, Abhijit; Mahanta, C.; Choudhury, R.; Bhattacharya, P. (2016)
© 2016 Taylor & Francis Group, London. The present study examines the groundwater chemistry, hydrogeochemical evolution and Arsenic (As) enrichment in shallow aquifers in the southern Brahmaputra river basin situated close to Naga-thrust belt. The major-ion composition dominated by a Na?Ca?HCO3 and Ca?Na?HCO3 hydro-chemical facies. Groundwater composition influenced by silicates weathering in S-region of Brahmaputra basin aquifers. The aquifers of S-region are severely contaminated with As (max 0.45 mg/L), nearly 92% collected groundwater sample are enriched with As. As show poor and negative correlation with various redox—sensitive solutes. It suggests that not a single process is controlling factor, although multiple biogeochemical mechanisms might influence As liberation and fate in groundwater of S-region. The geologic explanation for high arsenic in the southern region of Brahmaputra basin (upper Assam) is probably the crustal recycling of arsenic as an incompatible element during tectonic activity.